2010
DOI: 10.4074/s0003503310004021
|View full text |Cite
|
Sign up to set email alerts
|

Production de rythmes dans la schizophrénie : un déficit de l’alternance de temps

Abstract: Distribution électronique Cairn.info pour NecPlus. © NecPlus. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalable et écrit d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In both tasks however, patients were characterized by flatter gradients than controls, indicating less accurate and especially overall more variable timing capacities. Using a similar comparative method, Wilquin et al (2010) and Ameller et al (2011) also reported preserved perceptual detection of irregularities in otherwise regular sequences for interval shorter than 500ms, even if once more patients revealed overall more errors in their decision making.…”
Section: 4mentioning
confidence: 88%
See 3 more Smart Citations
“…In both tasks however, patients were characterized by flatter gradients than controls, indicating less accurate and especially overall more variable timing capacities. Using a similar comparative method, Wilquin et al (2010) and Ameller et al (2011) also reported preserved perceptual detection of irregularities in otherwise regular sequences for interval shorter than 500ms, even if once more patients revealed overall more errors in their decision making.…”
Section: 4mentioning
confidence: 88%
“…Another patient reported: "he would shoot gun fires towards his watch in order to kill time, which he considered as his worst enemy" (Minkowski, 1933, p. 13). More recently, a French psychologist transcribed examples of time distortions in young patients with Ultra High Risk of developing schizophrenia and with first-episode psychosis (15-25 years of age) for her PhD work (Wilquin, 2010). In her work, she reported, for example, a young patient who said to have found himself in front of closed gates at his high school on three different consecutive days, in the middle of the night.…”
Section: Experiential Distortions Of Time: Studying Verbatimmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet an additional possibility is that the overestimations and underproductions are a consequence of systematic memory distortions (Penney et al, 2000). Indeed, recent studies have observed significant correlations between the performance on time perception tasks and that found in neuropsychological outcomes typically affected in schizophrenia (e.g., Lee et al, 2009;Wilquin et al, 2010).…”
Section: 4mentioning
confidence: 99%